AB0451 Changes in DAS28, CDAI and SDAI are Associated with Biologic Class, Gender, Previous Biologic Therapy and ACPA/RF Status – Results from Reuma.PT. (10th June 2014) - Romao, V.; Santos, M.; Polido-Pereira, J.; Duarte, C.; Nero, P.; Miguel, C.; Costa, J.; Pimentel-Santos, F.; Barcelos, F.; Costa, L.; Melo Gomes, J.; Pereira da Silva, J.; et al.
Abstract : Background: Tocilizumab (TCZ) and anti-tumor necrosis factor (TNF) biologic agents are key therapies in the management of rheumatoid arthritis (RA). They are considered to be equally effective and very few head-to-head comparisons have been published. Objectives: To compare response to therapy in RA patients treated with anti-TNF agents and TCZ according to different response measures and determine the factors influencing it. Methods: We included RA patients registered in the Rheumatic Diseases Portuguese Register, Reuma.pt, who started anti-TNF or TCZ after January 1, 2008, were treated for at least 6 months and had available DAS28 scores at baseline and at 6 months. Our primary outcome was the change in DAS28, CDAI and SDAI at 6 months. We performed linear regressions to compare the groups and determined the best model predicting change in disease activity for each index. Results: 524 RA patients were enrolled, (106 adalimumab, 202 etanercept, 43 golimumab, 78 infliximab, 95 TCZ). At baseline, TCZ users were less frequently naïve to biologic therapies (54.7% vs. 85%, p<0.0001), had more swollen and tender joint counts (p<0.0001 and p=0.02, respectively) and higher disease activity according to all indexes: DAS28 6.1±1.1 vs. 5.4±1.3 (n=524, p<0.0001), CDAI 33.3±13.2 vs. 28.1±13.6 (n=376, p=0.005), SDAI.35.6±13.1 vs. 29.1±30.4 (n=361, p=0.004). At 6 months, change in DAS28, CDAI, SDAI and joint counts was significantly higher in the TCZ group (Table 1 ). Multivariate linear regression models best predicting change in disease activity included biologic class, number of previous biologics, baseline activity, gender and ACPA/RF status (Table 2 ). Compared to anti-TNF, TCZ was associated with a larger difference in ΔDAS28, ΔCDAI and ΔSDAI of, respectively, 1.45, 4.25 and 5.41. Conclusions: TCZ treatment was associated with greater change in DAS28, CDAI, SDAI and joint counts at 6 months. Biologic class, number of previous biologics, baseline activity, gender and ACPA/RF status predicted change in disease activity. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3414